DEVELOPMENT OF A MAINTENANCE POSSESSION SCHEDULER FOR A RAILWAY - Cillie, Dewald; Bekker, James (The South African Journal of Industrial Engineering, 2023)
Maintenance of rail infrastructure is an important element in rail operations to keep traffic moving. However, maintenance causes infrastructure to be taken out of service, which impacts traffic flow. In this study, the requirements of a maintenance possession scheduler for a South African application were investigated and a proposed solution was developed. The main objective of the scheduler was to minimise the deviation of the train service on a subset of rail infrastructure while ensuring that the required maintenance was done. An application case – the railway infrastructure between Bellville and Wellington in the Western Cape province of South Africa – was identified. A novel mixed-integer linear programming model that could do possession scheduling for 24 hours on a microscopic level was formulated for this case, and implemented in the software Cplex, after which it was validated. Finally, several experiments were conducted to investigate the model’s performance and the results. It was found that the model delivered optimal results in less than nine minutes, which makes it a feasible maintenance possession scheduler for day-to-day work in the immediate planning horizon.